Neoadjuvant chemotherapy, DEB-TACE, and 3D-printed prosthesis for primary pelvic pleomorphic undifferentiated sarcoma: a case report - Liu, Jiahui; Wang, Jiawen; Dai, Hui; Feng, Qi (Frontiers in Oncology, 2025)
Pleomorphic undifferentiated sarcoma (PUS) is a highly malignant soft tissue sarcoma typically found in the extremities or visceral organs, with primary pelvic cases being exceedingly rare and lacking standardized management strategies. We present the case of an elderly female with primary pelvic PUS who presented with right hip pain and progressive immobility. The tumor was large and involved surrounding tissues, making single-stage en bloc resection unfeasible. A multimodal strategy was implemented, including neoadjuvant chemotherapy combined with anlotinib, followed by drug-eluting bead transarterial chemoembolization (DEB-TACE), and subsequent resection and reconstruction with a 3D-printed pelvic prosthesis were performed. The patient achieved satisfactory functional recovery, and at the 12-month follow-up, there was no evidence of recurrence or metastasis and tumor was judged to have achieved pathological complete remission (pCR).This case demonstrates the feasibility of individualized multimodal therapy for complex pelvic PUS and provides valuable insights for managing this challenging entity.